(untitled) (Modern American Journal of Social Sciences and Humanities, 2025)
This article explores the modern principles of inclusive education, their pedagogical significance, and their implementation in the educational system of Uzbekistan. It analyzes the stages of development and practical directions of inclusive education based on national legal frameworks and state policies. The study compares advanced international experiences, UNESCO and UN data, and local practices. The article aims to contribute to the improvement of pedagogical approaches that support the development of inclusive education in Uzbekistan.